Hydrogen embrittlement of an interstitial equimolar high-entropy alloy. (15th May 2018) - Luo, Hong; Li, Zhiming; Lu, Wenjun; Ponge, Dirk; Raabe, Dierk
Graphical abstract: Highlights: Hydrogen embrittlement mechanism in an interstitial high-entropy alloy is revealed. Hydrogen enhanced localized plasticity is critical to the embrittlement. Both intergranular and transgranular fracture under hydrogen are observed. Aggregated nano-carbides are potential sites for crack initiation under hydrogen. Abstract: We investigated the hydrogen embrittlement mechanism in an interstitially carbon alloyed equimolar CoCrFeMnNi high-entropy alloy (HEA) through low strain rate tensile testing under in-situ hydrogen charging. The tensile ductility was significantly reduced by hydrogen charging. The failure mode of the interstitial HEA in presence of hydrogen was a combination of intergranular and transgranular fracture as well as microvoid coalescence. Aggregated nano-carbides act as potential sites for crack initiation. These findings show that the carbon alloyed equimolar high-entropy alloy is susceptible to hydrogen embrittlement.